PENGARUH DISIPLIN TERHADAP KINERJA PEGAWAI PADA DINAS PENANAMAN MODAL DAN PELAYANAN TERPADU SATU PINTU (DPMPTSP) KABUPATEN MERAUKE - Rusianti, Anita; Padan, Renie (Lembaga Penelitian dan Pengabdian Masyarakat Universitas Sains dan Teknologi Jayapura, 2020)
The Investment Office and the One Stop Integrated Service (DPMPTSP) of Merauke Regency have the task of providing guidance and developing the skills of the investment apparatus and actors in the field of investment, organizing guidance, monitoring, evaluating, reporting and controlling investment, organizing coordination of investment development, and administering office administration. This can be done by maximizing the performance of its employees by increasing discipline, such as supervision, coordination, motivation and so on so that employee performance increases. This disciplinary variable is closely related to the performance variable in achieving good service delivery to the community. The research sample is all employees in the Investment Office and the One Stop Integrated Service (DPMPTSP) of Merauke Regency with the research time period is February 2018. Data analysis techniques use multiple linear regression equations to test the hypothesis that discipline has a positive effect on employee performance in Investment Office and One Stop Integrated Services (DPMPTSP) of Merauke Regency. The results of the study showed that the motivational variable had a positive and significant effect on performance with the results of the regression ie Performance = 28,626 + 0,240X. Keywords: discipline, performance